Factors Influencing Blood Pressure Control in Older Adults Hypertension: A Systematic Review - Nurul Fauziah Handayani; Joni Haryanto; Dianis Wulan Sari (Indonesian Journal of Global Health Research, 2025)
Hypertension is the leading cause of premature death worldwide, and it increases with age, like many other chronic diseases. Poor blood pressure control behavior is the main cause of hypertension management failure. Objective: Hypertension significantly increases the risk of stroke and heart disease, which is a leading cause of death and disability globally, particularly among older adults. This review identified factors that influence blood pressure control behavior of the elderly with hypertension. Method: The PRISMA guidelines are used as a systematic search in PubMed, Scopus, Sage journals, Google Scholar and Science Direct in 2019 – 2024. The Joanna Briggs Institute's unified analytics framework was adopted for data synthesis. The population in this review is the elderly who suffer from hypertension. Results: A total of 17.542 articles were obtained from the four databases. sixteen articles were selected after extraction and incorporation of inclusion criteria. Conclusion: This review shows that economics, health literacy and education are the main factors in blood pressure control behavior in elderly people suffering from hypertension. Lessons from this review can help improve adherence to hypertension control, prevent health complications, and improve quality of life in the future.